2016
DOI: 10.1016/j.freeradbiomed.2016.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown delta-5-desaturase promotes the formation of a novel free radical byproduct from COX-catalyzed ω-6 peroxidation to induce apoptosis and sensitize pancreatic cancer cells to chemotherapy drugs

Abstract: Recent research has demonstrated that colon cancer cell proliferation can be suppressed in the cells that overexpress COX-2 via generating 8-hydroxyoctanoic acid (a free radical byproduct) during dihomo-γ-linolenic acid (DGLA, an ω-6 fatty acid) peroxidation from knocking down cellular delta-5-desaturase (D5D, the key enzyme for converting DGLA to the downstream ω-6, arachidonic acid). Here, this novel research finding is extended to pancreatic cancer growth, as COX-2 is also commonly overexpressed in pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 55 publications
(50 reference statements)
9
48
0
Order By: Relevance
“…FADS1, as the rate-limiting enzyme of PUFA synthesis, catalyzing DGLA to AA, was reported to be frequently dysregulated in cancers. FADS1 knockdown not only inhibited cancer growth and migration but also enhanced the cytotoxicity of chemotherapy drug [19][20][21]55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FADS1, as the rate-limiting enzyme of PUFA synthesis, catalyzing DGLA to AA, was reported to be frequently dysregulated in cancers. FADS1 knockdown not only inhibited cancer growth and migration but also enhanced the cytotoxicity of chemotherapy drug [19][20][21]55 .…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid desaturase 1 (FADS1) is the key rate-limiting enzyme of the bioactive metabolites which convert dihomo-gamma-linolenic acid (DGLA) to AA 18 . Previous studies have shown that the expression of FADS1 was dysregulated in many cancers and that knockdown of FADS1 not only inhibited cancer growth and migration but also enhanced the cytotoxicity of chemotherapeutic agents [19][20][21][22] . However, the molecular mechanism of FADS1 in laryngeal cancer still remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Western blot was used to assess the expression of Bcl-2, procaspase-9 and procaspase-3, γH2AX and acetyl histone 3 in BxPC-3 and its D5D- KD counterpart upon different treatments in vitro as described elsewhere [34] , [35] , [36] , [37] , [38] . For their expression in vivo, tumor tissues (~ 50–100 mg) were frozen in liquid nitrogen and crushed to a fine powder, then the protein was extracted using CelLytic™ lysis reagent.…”
Section: Methodsmentioning
confidence: 99%
“…Our lab recently discovered that COX-2-catalyzed DGLA peroxidation can produce the novel anti-cancer byproduct 8-hydroxyoctanoic acid (8-HOA), which can serve as a histone deacetylase inhibitor (HDACi) to inhibit cancer cell growth and metastasis in pancreatic cancer cells, e.g. , BxPC-3 [33] , [34] , [35] , [36] , [37] , [38] . However, the formation of 8-HOA from COX-catalyzed DGLA peroxidation can be limited by delta-5 desaturase (the rate-limiting enzyme to convert DGLA to AA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation